2014
DOI: 10.1007/s11695-014-1185-2
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Analgesia in Morbid Obesity

Abstract: Morbidly obese patients due to high incidence of obstructive sleep apnea (OSA) are predisposed to opioid induced airway obstruction and thus frontline high ceiling analgesics (opioids) have concerns based on safety in their liberal use. Although surgical techniques over the last two decades have seen a paradigm shift from open to laparoscopic procedures for morbidly obese patients; optimally titrated yet safe analgesic management still remains a challenge. The present review sums up the analgesic options avail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 64 publications
0
42
0
2
Order By: Relevance
“…15 However, it is imperative to balance the risk of opioid-induced adverse events with adequate analgesia to ensure that patients do not experience complications such as atelectasis and subsequent pneumonia due to pain. 1 The current study demonstrated that patients across the BMI spectrum experience similar levels of postoperative pain and consume similar amounts of narcotic analgesics during their postoperative inpatient stay. A similar result has been demonstrated by Armaghani et al, who determined that BMI was not a risk factor for increased opioid demand in the postanesthesia care unit (PACU) in patients who had undergone elective spinal surgery.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…15 However, it is imperative to balance the risk of opioid-induced adverse events with adequate analgesia to ensure that patients do not experience complications such as atelectasis and subsequent pneumonia due to pain. 1 The current study demonstrated that patients across the BMI spectrum experience similar levels of postoperative pain and consume similar amounts of narcotic analgesics during their postoperative inpatient stay. A similar result has been demonstrated by Armaghani et al, who determined that BMI was not a risk factor for increased opioid demand in the postanesthesia care unit (PACU) in patients who had undergone elective spinal surgery.…”
Section: Discussionmentioning
confidence: 58%
“…This concern is magnified in obese patients, who typically have increased comorbidities and a higher risk of obstructive sleep apnea. 1,15,18 Thus, these patients often require close monitoring of analgesic intake postoperatively to avoid opioid-induced respiratory depression and other opioid-related adverse events. 15 However, it is imperative to balance the risk of opioid-induced adverse events with adequate analgesia to ensure that patients do not experience complications such as atelectasis and subsequent pneumonia due to pain.…”
Section: Discussionmentioning
confidence: 99%
“…Obese patients show extreme sensitivity to even small doses of opioids [17]. Clinically significant respiratory depression increases proportionately with BMI and severity of OSA [71]. Worsening of OSA [72], postoperative respiratory obstruction [73], acute hypoxemia/hypercarbia, [74] delayed recovery [75], delayed discharge [76], increased postoperative nausea vomiting [77], and increased ICU admission rates [19] are among the few complications that have been directly attributed to perioperative opioid use in obese patients.…”
Section: Is There An Ideal Analgesic Regimen? Transfer From Pacu To Fmentioning
confidence: 99%
“…1,2 Given this background, multimodal analgesia is advocated for bariatric surgery with the aim of reducing opioid use. 3,4 At the time of writing, no studies were able to demonstrate a technique that can consistently remove the need for any postoperative opioid analgesia. In this study, we report the use of an anaesthesia protocol that allowed a significant proportion of our patients undergoing laparoscopic sleeve gastrectomy to be completely free from any long-acting potent opioids in the intra-operative and postoperative period.…”
Section: Introductionmentioning
confidence: 99%